Penilaian bahan pembelajaran sastera kontemporari bahasa inggeris darjah empat sekolah rendah - Mustafa, H.; Leng, C.H.; Darulsalam, G.; Ranee, A. (Faculty of Education, University of Malaya, 2013)
The purpose of this research aim to develop a web based learning in teaching and learning Year Four English Literature Components. The chosen topic for Year Four English Literature component is “Tidy your room, Tanya” The web based learning developed by using the ADDIE model. Five stages involved in the development of website are analysis, design, develop, implementation and evaluation. This research involved 60 students and two teachers from one primary school in the Jasin District of Malacca. Questionnaires were used to get the information needed. The objectives are the usage of Constructivism Learning Theory and collaboration strategy in the web based environment. The data collected show that collaboration strategy had been applied successfully in the web based learning environment. Student perception towards web based learning environment can be seen from the contents and interface design used in the learning environment. It is hoped that the development of this website will attract students in learning and teachers in teaching literature component which will also help them to acquire language skills. The result of this research shows that the development of the web based learning has achieved its goals with the specification outline in research objectives.